2021
DOI: 10.1016/j.jdermsci.2021.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons regulate the pigmentation pathway and induce DNA damage responses in keratinocytes, a process driven by systemic immunity

Abstract: aromatic hydrocarbons regulate the pigmentation pathway and iinduce DNA damage responses in keratinocytes, a process driven by systemic immunity,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…In this regard, it has been shown that tobacco smoke extract induced MMP-1 expression via activation of AhR signaling pathway in human fibroblasts and keratinocytes (Ono et al, 2013). Supportive evidence regarding the contribution of pollutants and tobacco to skin hyperpigmentation via ROS is also provided by multiple other studies (Vierkötter et al, 2010;Cho et al, 2012;Ishiwata et al, 2013;Delijewski et al, 2014;Peng et al, 2017;Leijs et al, 2018;Milani et al, 2019;Khmaladze et al, 2020;Krutmann et al, 2020;Suo et al, 2020;Yang et al, 2020;Chan et al, 2021;Grether-Beck et al, 2021;Moon et al, 2022) discussed in detail in Table 1.…”
Section: Oxidative Stress Pathwaysmentioning
confidence: 78%
See 1 more Smart Citation
“…In this regard, it has been shown that tobacco smoke extract induced MMP-1 expression via activation of AhR signaling pathway in human fibroblasts and keratinocytes (Ono et al, 2013). Supportive evidence regarding the contribution of pollutants and tobacco to skin hyperpigmentation via ROS is also provided by multiple other studies (Vierkötter et al, 2010;Cho et al, 2012;Ishiwata et al, 2013;Delijewski et al, 2014;Peng et al, 2017;Leijs et al, 2018;Milani et al, 2019;Khmaladze et al, 2020;Krutmann et al, 2020;Suo et al, 2020;Yang et al, 2020;Chan et al, 2021;Grether-Beck et al, 2021;Moon et al, 2022) discussed in detail in Table 1.…”
Section: Oxidative Stress Pathwaysmentioning
confidence: 78%
“…For example, genes targeted by AhR were shown to be induced by UVB irradiation ( Noakes, 2015 ). In sum, skin’s exposure to environmental stimuli can activate hyperpigmentation via AhR activation and subsequent increase of TYR activity, melanin synthesis, and upregulation of TYRP-1, DCT, and MITF expression ( Krutmann et al, 2008 ; Luecke et al, 2010 ; Nakamura et al, 2013 ; Nakamura et al, 2016 ; Abbas et al, 2017 ; Leijs et al, 2018 ; Chan et al, 2021 ; Shi et al, 2021 ; Ahn et al, 2022 ) ( Table 1 ).…”
Section: Intracellular Signaling Pathways Crosstalk: Impacts Of Air P...mentioning
confidence: 99%
“…Previous studies also have shown that UVB affected epidermal morphology, disrupted the skin barrier, increased transepidermal water loss, and decreased stratum corneum hydration ( 31 ). Initially, melanin pigmentation plays a dual role in skin:it is suggested to render photoprotection from the DNA-damaging effects of UV ( 32 , 33 ) while leading to acquired hyperpigmentation disorders such as melasma ( 34 , 35 ). In this context, consumers have an increasing requirement for quality natural cosmetic material.…”
Section: Discussionmentioning
confidence: 99%
“…PAHs, a type of toxic constituents in PM, are known to be potential carcinogens and the main cause of lung cancer in the PM-exposed population, the underlying mechanism may include immune impairments. 40,41 Due to its sensitivity and specificity, urinary 1-OHP is usually used as a biomarker to evaluate high PAH exposure. 42 We found that urinary 1-OHP negatively associated with the levels of GATA3 or T-bet.…”
Section: Discussionmentioning
confidence: 99%